Effect of Herbal Feed Additives on Goat Milk Volatile Flavor Compounds - Jacek Antoni Wójtowski; Małgorzata Majcher; Romualda Danków; Jan Pikul; Przemysław Mikołajczak; Marta Molińska-Glura; Joanna Foksowicz-Flaczyk; Agnieszka Gryszczyńska; Zdzisław Łowicki; Karolina Zajączek; Grażyna Czyżak-Runowska; Maria Markiewicz-Kęszycka; et al. (Foods, 2023)
The aim of this study is to investigate the effects of herbal supplements administered to goats on sensory quality and volatile flavor compounds in their milk. The experiment was conducted on sixty Polish white improved goats randomly allocated into five feeding groups (four experimental and one control) of twelve goats each. The trial lasted 12 weeks. The experimental animals received supplements containing a mixture of seven or nine different species of herbs at 20 or 40 g/animal/day. The control group received feed without any herbal supplements. Milk obtained from experimental and control groups of animals was characterized by a low content of aroma compounds, with only 11 chemical compounds being identified. Decanoic methyl ester, methylo 2-heptanone and methylo-butanoic methyl ester had the highest share in the total variability of the tested aroma compounds (PCA). During the sensory evaluation, the smell and taste of most of the samples were similar (p > 0.05). However, the addition of herbal feed supplements lowered the concentration of Caproic acid (C6:0), Caprylic acid (C8:0) and Capric acid (C10:0), which caused a significant reduction in the goaty smell of milk. The obtained results indicate that the studied herbal supplements can reduce the intensity of goaty smell and allow goat milk production without modification of other sensory features.